Assimilative capacity of the atmosphere at Lucknow with respect to air pollution - NANDANKAR, P .K. (MAUSAM, 1999)
The present study aim at seasonal and diurnal pollution potential at Lucknow, the capital of Uttar Pradesh. To assess the pollution potential, meteorological data for five year period (1982-86) of Lucknow have been analyzed for four season, viz.; Winter (December-February), Summer (March-May), Southwest Monsoon (June-September) and Post Monsoon (October-November). Seasonwise wind roses, stability, stability wind roses have been prepared and season wise diurnal variation of mixing height and ventilation coefficient have also been worked out. It is found that Lucknow has a better diffusion capacity in summer and poor in winter. Afternoon hours are better for vertical mixing. The winds are predominant from west to north direction in all season except in monsoon where it blows from east direction.